Impact of Service Quality on Customer Satisfaction towards Online Banking - Chua Man Ling,; Siti Norziah Ismail, (Research in Management of Technology and Business, 2021)
Online banking services are popular around the world. In Malaysia, the number of online users has increased rapidly. In this research, researcher will investigate the service quality dimension affect that customer satisfaction in online banking. Moreover, the main objective is to determine the impact of responsiveness, trust, convenience, efficiency and security towards the dependent variable, which is customer satisfaction in online banking. Contribution of the study helps the banking institutions to enhance and improve their online banking services based on this study. This study extended the SQ model of SERVQUAL proposed by Vetrivel et al., (2019). This study employs convenient sampling techniques which involved user of online banking system in Batu Pahat. In this research, researcher was used the quantitative research data collection method to collect the data through Google form. A total of 262 online questionnaires was collected for this study. Descriptive analyses was used in this study. Furthermore, the result of statistical analyses was obtained by utilizing the Statistical Package for Social Sciences (SPSS). The empirical result shows that all of IV in this research have a positive impact on DV in online banking. The convenience was the most influence customer satisfaction among five IV whereas responsiveness was the weakest. In this study, the findings are useful for bank institutions to make decision making in future and understand what customers’ needs. With limitation of sample size population, for future researchers can investigate a bigger population such as different state in Malaysia